2008
DOI: 10.1021/ma800500u
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Polyaniline Multidimensional Architectures: From Plate-like Structures to Flower-like Superstructures

Abstract: Polyaniline multidimensional architectures from plate-like structures to flower-like superstructures have been successfully tailored by the oxidation polymerization in dilute aniline solution at room temperature, when the molar ratio of oxidant to monomer was altered in the range of 0.1:1-0.8:1. It was found that at low molar ratio (0.1:1-0.3:1) plate-like structures could be synthesized, while the as-synthesized product at the higher molar ratio (0.4:1-0.8:1) was flower-like superstructures; and the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 31 publications
(50 reference statements)
1
59
0
2
Order By: Relevance
“…In the present communication, we have successfully developed a simple, novel, low-cost, and environmentally benign strategy to produce sheet-like PANI with controllable sizes by recycling the discharged liquids. Interestingly, unlike the previously reported synthesis methods for PANI micro/nanostructures in which oxidants such as ammonium peroxydisulfate (APS), horseradish peroxidase, and ferric chloride were needed and were crucial to obtain different morphologies of PANI micro/nanostructures, [20][21][22] the driving force used here, hydrogen bonding and high oxidation state aniline oligomers, are low-cost and environmentally friendly. A plausible formation mechanism of sheet-like PANI is proposed, which provides some novel insights into the PANI morphology and might be helpful for the assembly of other micro/nanometerials.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present communication, we have successfully developed a simple, novel, low-cost, and environmentally benign strategy to produce sheet-like PANI with controllable sizes by recycling the discharged liquids. Interestingly, unlike the previously reported synthesis methods for PANI micro/nanostructures in which oxidants such as ammonium peroxydisulfate (APS), horseradish peroxidase, and ferric chloride were needed and were crucial to obtain different morphologies of PANI micro/nanostructures, [20][21][22] the driving force used here, hydrogen bonding and high oxidation state aniline oligomers, are low-cost and environmentally friendly. A plausible formation mechanism of sheet-like PANI is proposed, which provides some novel insights into the PANI morphology and might be helpful for the assembly of other micro/nanometerials.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, Guo and co-workers reported that sheet-like structures could be prepared by template-free polymerization in dilute aniline solution. [20] However, the low product efficiency that resulted from the low aniline concentration and the rigorous molar ratio of oxidant to monomer might restrict its practical and extensive application. Therefore, the design and synthesis of PANI micro/nanosheets by a template-free method is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline has various advantages such as simple synthetic process, low cost, good stability in the air, and relatively high electrical conductivity. Polymerization mechanism [6][7][8], surface structure [9][10][11][12][13][14][15][16][17][18], synthesis of nano-composite [19][20][21], and chiroptical properties of polyaniline [22] have been studied. Polymerization of aniline under different conditions allows formation of various fine surface structures [23].…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, las nanofibras de polianilina han demostrado tener mayor sensibilidad y menor tiempo de respuesta que los films tradicionales cuando son usados como sensores de gases [81]. Diferentes nanoestructuras 1-D han sido obtenidas en bibliografía por métodos de oxidación química, como por ejemplo: estructuras en forma de plato [82], en forma de hoja [83], nanocopos [84], nanofibras [84][85][86][87][88][89][90], nanotubos [91,92], nanoesferas [83,88,93] o rectángulos recubiertos con formas nanoestructuradas [94]. La agregación o el crecimiento de diferentes micro o nanoestructuras puede crear estructuras 3-D.…”
Section: Polímeros Conductores Nanoestructuradosunclassified
“…Estructuras en forma de flor [82,86], en forma de champiñón [92], en forma de caja compuesta de nanofibras [85] y microesterillas de nanofibras [87] han sido obtenidas.…”
Section: Polímeros Conductores Nanoestructuradosunclassified